A genome-wide association study implicates NR2F2 in lymphangioleiomyomatosis pathogenesis. Issue 6 (27th June 2019) - Kim, Wonji; Giannikou, Krinio; Dreier, John R.; Lee, Sanghun; Tyburczy, Magdalena E.; Silverman, Edwin K.; Radzikowska, Elżbieta; Wu, Shulin; Wu, Chin-Lee; Henske, Elizabeth P.; Hunninghake, Gary; Carel, Havi; et al.
Introduction: Lymphangioleiomyomatosis (LAM) occurs either associated with tuberous sclerosis complex (TSC) or as sporadic disease (S-LAM). Risk factors for development of S-LAM are unknown. We hypothesised that DNA sequence variants outside of TSC2 / TSC1 might be associated with susceptibility for S-LAM and performed a genome-wide association study (GWAS). Methods: Genotyped and imputed data on 5 426 936 single nucleotide polymorphisms (SNPs) in 426 S-LAM subjects were compared, using conditional logistic regression, with similar data from 852 females from COPDGene in a matched case–control design. For replication studies, genotypes for 196 non-Hispanic White female S-LAM subjects were compared with three different sets of controls. RNA sequencing and immunohistochemistry analyses were also performed. Results: Two noncoding genotyped SNPs met genome-wide significance: rs4544201 and rs2006950 (p=4.2×10 −8 and 6.1×10 −9, respectively), which are in the same 35 kb linkage disequilibrium block on chromosome 15q26.2. This association was replicated in an independent cohort. NR2F2 (nuclear receptor subfamily 2 group F member 2), a nuclear receptor and transcription factor, was the only nearby protein-coding gene. NR2F2 expression was higher by RNA sequencing in one abdominal LAM tumour and four kidney angiomyolipomas, a LAM-related tumour, compared with all cancers from The Cancer Genome Atlas. Immunohistochemistry showed strong nuclear expression in both LAM and angiomyolipoma tumours. Conclusions: SNPs on chromosome 15q26.2 are associated with S-LAM, and chromatin and expression data suggest that this association may occur through effects on NR2F2 expression, which potentially plays an important role in S-LAM development. GWAS identified alleles of two SNPs near NR2F2 that were associated with sporadic lymphangioleiomyomatosis. NR2F2 is a transcription factor that is expressed highly in both LAM and a LAM-related tumour, and NR2F2 is a new LAM gene. http://ow.ly/87xx30oiVhZ